Realizacja marksowskiej koncepcji wolności w państwie demokracji socjalistycznej - Strużyński, Krzysztof (2019)
The text gives an account of Marx’s attitude towards the theme of „freedom" in his works. It points out the significant differences in the approach to that topic at different stages of his political activity and important historical circumstances that influenced the approach to the problem. It analyzes individual works of Marx chronologically, revealing a more and more mature attitude to the issue of „freedom". Then, tries to fit Marx’s final definition of „freedom” into the philosophy of Lenin - Marxism-Leninism. It systematises the views on socialist democracy in the context of Marxism-Leninism philosophy and juxtaposes it with the democracies of capitalist countries. The author points out the major differences between socialist and liberal democracy, and different views on criticisms of the latter
Keywords: demokracja socjalistyczna; wolność; marksizm; leninizm; socjalizm